2021
DOI: 10.1590/s0004-2803.202100000-14
|View full text |Cite
|
Sign up to set email alerts
|

Results of Immunohistochemistry in the Differential Diagnosis of Early Hepatocellular Carcinoma and Nodules With High-Grade Dysplasia in Patients With Cirrhosis

Abstract: BACKGROUND: Hepatocellular carcinoma (HCC) is the most frequent primary cancer of the liver and cirrhosis is considered a pre-malignant disease. In this context, the evolutionary sequence from low grade dysplastic nodule and high grade dysplastic nodule (HGDN) to early HCC and advanced HCC has been studied. The differential diagnosis between HGDN and early HCC is still a challenge, especially in needle biopsies OBJECTIVE: To evaluate an immunohistochemistry panel to differentiate dysplastic nodules and HCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Glutamine synthetase could distinguish atypical nodules, early diagnosis, and invasion of HCC. For instance, GS is considered to have high specificity and sensitivity to the differential diagnosis of HCC and dysplastic nodules ( Coral et al, 2021 ). Glypican-3, heat shock protein 70, and GS are utilized to distinguish a <2 cm hepatocellular lesion without classic radiological characters of HCC with cirrhosis by immunochemistry (IHC) or designed RNA probes ( Tremosini et al, 2012 ; Di Tommaso and Roncalli, 2017 ; Bakheet et al, 2020 ).…”
Section: The Components Of Glutamine Metabolism As Biomarkers Of Hccmentioning
confidence: 99%
“…Glutamine synthetase could distinguish atypical nodules, early diagnosis, and invasion of HCC. For instance, GS is considered to have high specificity and sensitivity to the differential diagnosis of HCC and dysplastic nodules ( Coral et al, 2021 ). Glypican-3, heat shock protein 70, and GS are utilized to distinguish a <2 cm hepatocellular lesion without classic radiological characters of HCC with cirrhosis by immunochemistry (IHC) or designed RNA probes ( Tremosini et al, 2012 ; Di Tommaso and Roncalli, 2017 ; Bakheet et al, 2020 ).…”
Section: The Components Of Glutamine Metabolism As Biomarkers Of Hccmentioning
confidence: 99%
“…GPC3 is a carcinoembryonic antigen, a member of the phosphatidylinositol proteoglycan family of membrane-bound acetylated heparan sulfate proteoglycans, expressed in fetal liver and progenitor cells as well as in many HCC cases and other tissues [ 33 ]. According to a study by Coral et al, GPC3 has a sensitivity of approximately 65% and a specificity of 96% for diagnosing HCC [ 3 ]. Immunohistochemistry and a real-time reverse transcription-polymerase chain reaction showed that the expression levels of GPC3 were much greater in small HCC than in cirrhosis and other categories of minor lesions.…”
Section: Diagnosis Of Precancerous Lesions Of Hccmentioning
confidence: 99%
“…Precancerous lesions are characterized by a multistep process ranging from dysplastic nodule (DN) to early HCC and finally to advanced HCC [ 2 ]. Cirrhosis was considered a precancerous condition associated with a high probability of developing HCC [ 3 ]. Although liver transplantation, ablation, and surgical resection have achieved good 5-year survival rates in the treatment of early-stage HCC, only about 20% of patients with HCC are diagnosed in the very early and early stages.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 The addition of the fourth marker to this panel, that is clathrin heavy chain (CHC), was associated with a gain in sensitivity and specificity for the diagnosis of early-HCC from DNs in liver biopsy. 45,46 The angiogenic markers CD34, CD31 and CD105 improve the assessment of tumour neovascularization, a surrogate marker of malignant transformation in HCC. 6,47 However, the gradual increase in their expression between HGDNs, early-HCCs and well-differentiated HCCs, limits its power of discrimination.…”
Section: Histological Diagnostic Challengementioning
confidence: 99%
“…The overall sensitivity and specificity for the diagnosis of early‐HCC of at least two markers being positive were 70% and 100%, respectively 43,44 . The addition of the fourth marker to this panel, that is clathrin heavy chain (CHC), was associated with a gain in sensitivity and specificity for the diagnosis of early‐HCC from DNs in liver biopsy 45,46 …”
Section: Mechanisms Of Malignant Transformation Into Hccmentioning
confidence: 99%